The role of globalization in shaping achievements towards the values of citizenship and integrity (Journal of the College of Basic Education, 2023)
The study aimed to determine the role of globalization in shaping attitudes towards the values of citizenship and integrityFrom the point of view of secondary school teachers in the light of some variables through a studyfield in Baghdad.To achieve this, the study sought to answer the following questions:Q1/ To what extent are secondary school teachers aware of globalization and its dimensions: (Educational ©psychological; social; economic)?Q2/ Is there a statistically significant difference in the extent of secondary school teachers' awareness of globalization?Its dimensions: (educational, psychological, social, and economic); According to the variables: sex©academic qualification; And the Andrian experience?Q2/ What are the attitudes of secondary school teachers towards the values of citizenship in its dimensions: (legal, dpolitical; social; and patriotism)?Q4/ Is there a statistically significant difference in the attitudes of secondary school teachers towards values?Citizenship in its dimensions: (legal, political, social, and national); According to variables:sex; academic qualification; And teaching experience?Q5/ What are the attitudes of secondary school teachers towards integrity?